PERKEMBANGAN TARI KLASIK GAYA YOGYAKARTA DI ERA GLOBAL - Titik Putraningsih (FBS UNY, 2007)
The development of Yogyakarta classical dances in this global era is influenced by the advance of technology, the spread of tourism industries and the change of aesthetic taste of urban society. This article discusses how art lovers and artists face the global challenges and survive in the era. Dance experts create innovative forms of dances that are easy to learn; Dance organizations establish educational programs for dance learning; Dance education produces individuals who grow into dancers, or teachers in both formal and informal education. Moreover, dance organizations also produce new generation who will maintain, preserve and develop the classical dances in the future. Key Words: Yogyakarta classical dances, dance organizations, the global era